2018
DOI: 10.1021/acs.jpcc.8b02096
|View full text |Cite
|
Sign up to set email alerts
|

Tungsten Carbide as a Highly Efficient Catalyst for Polysulfide Fragmentations in Li–S Batteries

Abstract: The sluggish disproportionation of short-chain lithium polysulfides, Li 2 S x , is known to be one of the major causes to limit the rate capability of lithium−sulfur batteries. Herein, we report that tungsten carbide not only affords strong sulfiphilic surface moieties but also provides an efficient catalysis to enhance the polysulfide fragmentation, leading to a drastic improvement in the electrode kinetics. We show that tungsten carbide acts as a superb anchoring material for the long-chain polysulfide and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 63 publications
(99 reference statements)
1
24
0
Order By: Relevance
“…[62] Spired by good performance delivered by carbide with low cost, Huang and co-workers found another material (Mo 2 C) as catalyst and absorbent for LiPSs. [62] Spired by good performance delivered by carbide with low cost, Huang and co-workers found another material (Mo 2 C) as catalyst and absorbent for LiPSs.…”
Section: Adsorption-catalysis Synergymentioning
confidence: 99%
See 1 more Smart Citation
“…[62] Spired by good performance delivered by carbide with low cost, Huang and co-workers found another material (Mo 2 C) as catalyst and absorbent for LiPSs. [62] Spired by good performance delivered by carbide with low cost, Huang and co-workers found another material (Mo 2 C) as catalyst and absorbent for LiPSs.…”
Section: Adsorption-catalysis Synergymentioning
confidence: 99%
“…In order to anchor LiPSs effectively, Kim et al showed that tungsten carbides (WC) can not only catalyze the disproportionation of polysulfide but also capture the soluble LiPSs. Further study indicated that WC could accelerate the reaction 2normalS426normal/7normalS82+8normal/7normalS12 which is the “bottleneck” reaction of the three main reactions during the discharge process . Spired by good performance delivered by carbide with low cost, Huang and co‐workers found another material (Mo 2 C) as catalyst and absorbent for LiPSs.…”
Section: Adsorption‐catalysis For Thiosulfate or Polythionate Generationmentioning
confidence: 99%
“…Metal carbides and other metal compounds: The surface of WC is sulfiphilic, and WC could be used as effective catalyst to improve the electrode reaction kinetics by modulating the LiPS fragmentation [203] . As presented in Fig.…”
Section: Polar Sulfur Hostsmentioning
confidence: 99%
“…Copyright 2015, Wiley-VCH.(C) Schematic drawing describing the enhanced kinetics of composite electrode with WC used as additive.(D) Rate capability of the bare electrode, WC electrode, WC electrode with C-coated separator and WC electrode with C/WC-coated separator cells. Reprinted with permission from (Choi et al., 2018). Copyright 2018, American Chemical Society.…”
Section: Introductionmentioning
confidence: 99%
“…reported that tungsten carbide (WC) was used as a cathode additive to enhance the electrochemical performance (reversible capacity and rate capability) of LSBs (Choi et al., 2018). This study demonstrated that WC could offer the strong sulfiphilic surface moieties to entrap dissolved polysulfides.…”
Section: Introductionmentioning
confidence: 99%